Zemstvo of Ufa Governorate in 1917 - G. B. Azamatova (Научный диалог)
The article is devoted to the study of the history of Zemstvo institutions of the Ufa province in the period from February to October 1917. The role of zemstvo in the system of local governance, democratization of zemstvo assemblies and councils, as well as the formation of the volost zemstvo are examined. The research urgency is caused by the connection of this topic with the problem of the revolutionary crisis of 1917 in different regions of Russia. It is shown that in the period from February to October zemstvo institutions retained the organizational and managerial functions, but quickly lost their political positions. During this period the main controls were zemstvo council, which coordinated the activities for the reorganization of volost administration and the creation of organs of food with the participation of the population. Zemstvo assemblies felt the pressure of radical parties and representatives of the national movement. Where there were no cohesive groups enfranchised vowels, for example, in Zlatoust uyezd, zemstvo institutions became the spokesmen for farm interests. The democratization of zemstvo institutions and the formation of the volost zemstvo self-government could not prevent the collapse of the former system of management, separate parts of which (the departments of land management, their scientific and practical base) were used in the creation of new organs of power.